THE ROLE OF AI POWERED PERSONALIZATION IN ENHANCING CUSTOMER EXPERIENCE: A CROSS INDUSTRY ANALYSIS - Hariandi, Chandra; Asrori, Ali (Penelitian dan Pengembangan Ilmu, 2025)
Artificial intelligence (AI) has rapidly reshaped marketing, with over 74% of global marketers expected to adopt AI by 2025. Among its most transformative uses is AI-powered personalization, which can increase customer loyalty by 20% and retention by 19%. However, most studies remain limited to single industries, overlooking cross-sectoral differences in adoption, effectiveness, and customer expectations. This study analyzes how AI personalization influences customer experience across industries, identifies moderating contextual factors, and proposes best practices. Using a narrative review approach, literature from major databases (2015–2025) was examined through thematic synthesis and conceptual mapping. Findings show that AI personalization enhances emotional and behavioral responses and perceived effectiveness. Its impact, however, varies by sector—driven by differences in technology infrastructure, customer needs, and data regulations. AI personalization holds significant potential but requires context-sensitive implementation tailored to industry-specific challenges and expectations.